Can heme oxygenase-1 be a prognostic factor in patients with hepatocellular carcinoma? - Park, Cheon-Soo (Medicine (Baltimore), 2019)
Heme oxygenase-1 (HO-1) is an important catalytic enzyme in heme degradation, which increases during stressful conditions. It plays a major role in antioxidative and antiapoptotic processes and is associated with tumor growth and metastasis. This study aimed to evaluate the degree of HO-1 expressions in hepatocellular carcinoma (HCC) surgical specimens and the correlation between HO-1 expression and patient prognosis. Formalin-fixed, paraffin-embedded HCC tissue samples (n = 96) were included in the analysis, and the expression of HO-1 was evaluated by immunohistochemical staining. We reviewed clinical features of patients and evaluated the prognostic role of HO-1 in patient survival and recurrence. Positive HO-1 expression was identified in 43 cases (44.8%) and was frequently found in patients with advanced histology (Edmondson–Steiner [E-S] grade 2, 3, 4), α-fetoprotein (AFP) level of more than 200 IU/mL, and the presence of microvascular and capsular invasion (P < .05). In the univariate analysis, the overall survival (OS) and disease-free survival (DFS) of patients with HO-1-positive HCC were not statistically different from those with HO-1-negative HCC. Moreover, HO-1 expression was not associated with patient survival and recurrence based on the multivariate analysis. In the subgroup analysis of patients without preoperative transarterial chemoembolization (TACE) (n = 61), HO-1 was not also associated with tumor recurrence (P = .681). The clinical implication of HO-1 activity is controversial in various malignancies. However, HO-1 expression did not seem to influence the prognosis of HCC patients.